(untitled) (Scientific journal of the Fergana State University, 2023)
The successful progression of tourist plosis during the training field operation is much larger than the importance of management of general organizational requirements, as well as the hygienic rules of drug lives. This article used research and analysis methods such as generalization, pedagogical monitoring, comparative analysis, experimental, testing, pedagogical monitoring. Specialist organizations are held in the form of theoretical and practical training, and the historical development of tourism, technical, tactical, technical training, nature protection, social protection, socially useful work, socially useful, Information on hygienic doctrine, first medical care, forms and methods of organization of tourist plugs is provided.